2013
DOI: 10.1007/s11302-013-9370-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced striatal ecto-nucleotidase activity in schizophrenia patients supports the “adenosine hypothesis”

Abstract: Schizophrenia (SZ) is a major chronic neuropsychiatric disorder characterized by a hyperdopaminergic state. The hypoadenosinergic hypothesis proposes that reduced extracellular adenosine levels contribute to dopamine D 2 receptor hyperactivity. ATP, through the action of ecto-nucleotidases, constitutes a main source of extracellular adenosine. In the present study, we examined the activity of ecto-nucleotidases (NTPDases, ecto-5′-nucleotidase, and alkaline phosphatase) in the postmortem putamen of SZ patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Actually, reduced striatal ecto‐nucleotidase activity in schizophrenia patients supports the ‘hypo‐adenosinergic hypothesis’ (Aliagas et al . ), as catabolism of extracellular ATP or AMP by ecto‐nucleotidases near A2A receptors seems related to the activation of the receptors (Augusto et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Actually, reduced striatal ecto‐nucleotidase activity in schizophrenia patients supports the ‘hypo‐adenosinergic hypothesis’ (Aliagas et al . ), as catabolism of extracellular ATP or AMP by ecto‐nucleotidases near A2A receptors seems related to the activation of the receptors (Augusto et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, adenosine's crucial roles in synaptic/non-synaptic transmission in basal ganglia are recognized (see Sperl agh and Vizi 2011). Actually, reduced striatal ecto-nucleotidase activity in schizophrenia patients supports the 'hypo-adenosinergic hypothesis' (Aliagas et al 2013), as catabolism of extracellular ATP or AMP by ecto-nucleotidases near A2A receptors seems related to the activation of the receptors . In agreement with such a view, it has been demonstrated that the ecto-nucleotidases involved in adenosine formation in proximity of A2A receptors are abundant in striatal gliosomes , consistent with the involvement of glial A2A receptors in the disease pathophysiology (see also Rial et al 2014).…”
Section: Astrocytic A2a and D2 Receptors Form Receptor Heteromersmentioning
confidence: 91%
“…Striatal astrocytes express the heterodimer native receptors A2A-D2 (Cervetto et al, 2017). D2 receptors inhibit presynaptic glutamate release, while A2A receptor activation eliminates the effect of D2 receptor activation (Aliagas et al, 2013). A study was carried out using a synthetic peptide VLRRRRRKRVN, corresponding to the receptor region involved in the electrostatic interaction between A2A and D2 receptors.…”
Section: Adenosine Systemmentioning
confidence: 99%
“…A link between ADO hypofunction and SZ is supported by clinical evidence demonstrating increased enzymatic degradation of adenosine in SZ patients (Brunstein et al, 2007; Dutra et al, 2010). Most recently, reduced striatal ecto-nucleotidase (adenosine producing enzyme) activity was found in schizophrenia patients (Aliagas et al, 2013). A meta-analysis of six randomized controlled trials comparing adenosine modulators with placebo as adjuvant therapy in patients with schizophrenia demonstrated benefits in overall psychopathology (especially positive symptoms) in schizophrenia (Hirota and Kishi, 2013).…”
Section: Adenosine-dependent Mechanisms and Therapeutic Applicationsmentioning
confidence: 99%